IMPROVING YOUTH’S INTELLECTUAL AND CREATIVE SKILLS THROUGH THE FINE ARTS - Umirov Abdunazar Atabayevich (Galaxy International Interdisciplinary Research Journal, 2023)
This article talks about the issues of thinking of young people, increasing their creative-intellectual potential of freely expressing their thoughts through visual arts.